'Gemoy' Campaign Strategy: Norman Fairclough's Critical Discourse Analysis - Adam Yogantara; Dewi Kusumaningsih; Muhlis Fajar Wicaksana (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
Linguistically,